2013
DOI: 10.1016/j.jtcvs.2012.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal life support in patients with severe trauma: An advanced treatment strategy for refractory clinical settings

Abstract: From our data, ECLS seems to be a valuable option to resuscitate patients with severe trauma when conventional therapies are insufficient. ECLS is safe, feasible, and effective in providing hemodynamic support and blood gas exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 28 publications
2
43
1
Order By: Relevance
“…17 Only a few small series have argued that ECMO support could improve outcome in patients with disastrous trauma with coexisting chest injury or bleeding shock. 9,27,28 The preservation of major organ function by ECMO may indeed provide a better chance for survival in these patients. The present study showed a better outcome in this group of patients, especially when they survived the first month.…”
Section: Discussionmentioning
confidence: 99%
“…17 Only a few small series have argued that ECMO support could improve outcome in patients with disastrous trauma with coexisting chest injury or bleeding shock. 9,27,28 The preservation of major organ function by ECMO may indeed provide a better chance for survival in these patients. The present study showed a better outcome in this group of patients, especially when they survived the first month.…”
Section: Discussionmentioning
confidence: 99%
“…A secure implantation of VA-ECLS is also necessary to prevent blood loss via the cannulation sites. Cannulation sites hemorrhage related to mal-cannulation is a possible explanation of the high failure rate (29%, 4/14) of VA-ECLS in a practice adopting percutaneous Seldinger technique exclusively [7], as seen in our case 4. The man was found unconscious without obvious injuries in the woods.…”
Section: Discussionmentioning
confidence: 93%
“…VA-ECLS here is a desperate attempt to save patients from irreversibility and the decision to activate it is often made under time pressure [7,8]. Owing to the wide variety of presenting injuries and their corresponding managements, establishing an integrated protocol of VA-ECLS in traumatology can only be learned by exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case reports and small case series describe the use of ECLS in the management of pediatric and adult traumatic respiratory failure including blunt and penetrating parenchymal and tracheobronchial injuries [1][2][3][4][5][6][7][8][9][10], cardiac contusions [11][12][13], traumatic brain injury [14][15][16][17], and shock [18][19][20]. Retrospective cohort studies of trauma patients cared for at tertiary care referral centers report survival after ECLS ranging from 50-79% [21][22][23][24]. These case reports, small case series, and retrospective reviews suggest a potential role for ECLS in the management of traumatically injured patients.…”
Section: Introductionmentioning
confidence: 99%